Inventarisasi Tumbuhan Famili Apocynaceae Di Komplek Cipadung Permai Kota Bandung - Haikal Azmi; Hanna Kamillah Suwarna; Ateng Supriatna (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Apocynaceae is a family of plants with characteristics of producing white rubber, having leaves face-to-face or circular, large flowers of striking colors, slightly fragrant scents, as well as crowns The flower consists of five parts. The family has 155 tribes and more than 2,000 species. The Permai complex is a residential complex located in the town of Bandung. Family inventory Apocynaceae is carried out in the area of the Permai complex plant, considering the plants of this family have various benefits. The method used is the exploration and line transect method. This is done by comparing the morphology of plants with references on the Internet. From Results 3 individuals of Allamanda cathartica L and 8 individuals of the species Catharanthus were found.